Better vocabulary in 30 minutes a day - Schwager, Edith (Better English series., 2011)
Better Vocabulary in 30 Minutes a Day offers a comprehensive method for adding a more impressive list of words to your everyday speech and how to use them effortlessly and accurately. Besides giving definitions, this invaluable guide provides roots, stems, and elements of words so that you can increase your vocabulary with thousands of new words. Sprinkled throughout the book are fascinating stories about words and origins.